Earnings management, audit adjustments, and the financing of corporate acquisitions: Evidence from China - Lennox, Clive; Wang, Zi-Tian; Wu, Xi (Journal of Accounting and Economics, 2018)
Acquirers are motivated to overstate earnings prior to stock-financed acquisitions. We hypothesize that audits help to detect and correct such overstatements. We test this using a difference-in-differences design, which compares audit adjustments to earnings for stock-financed and cash-financed acquirers before versus after the acquisitions. Consistent with our hypothesis, we find larger downward adjustments in the audits immediately before stock-financed acquisitions. Further analysis of regulatory sanctions suggests the downward adjustments are in fact warranted, rather than auditors being overly conservative. Moreover, modifications in audit reports suggest that downward adjustments do not correct all of the reporting irregularities in audited financial statements.